2010
DOI: 10.1095/biolreprod.110.088229
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Aging Is Detrimental to Mouse Spermatogonial Stem Cell Function

Abstract: The development of techniques to maintain the spermatogonial stem cell (SSC) in vivo and in vitro for extended periods essentially allows for the indefinite continuation of an individual germline. Recent evidence indicates that the aging of male reproductive function is due to failure of the SSC niche. SSCs are routinely cultured for 6 mo, and no apparent effect of culture over this period has been observed. To determine the effects of SSC aging, we utilized an in vitro culture system, followed by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Derivation of GS cells in a B6 background is notoriously difficult (Kanatsu-Shinohara et al 2003). Its success depends on the batch of BSA (Kubota et al 2004), and SSC frequency is significantly reduced with enhanced aging (Schmidt et al 2011;Aoshima et al 2013). Using B6 mice as a model, we found that PS48 reliably establishes GS cells in a B6 background irrespective of the BSA batch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivation of GS cells in a B6 background is notoriously difficult (Kanatsu-Shinohara et al 2003). Its success depends on the batch of BSA (Kubota et al 2004), and SSC frequency is significantly reduced with enhanced aging (Schmidt et al 2011;Aoshima et al 2013). Using B6 mice as a model, we found that PS48 reliably establishes GS cells in a B6 background irrespective of the BSA batch.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, although SSCs in a B6 background increase modestly in number following serial transplantation, GS cells cannot be established under the conventional culture conditions. Although adding GFRA1 reportedly enhanced self-renewal (Kubota et al 2004), cultured cells could be maintained for only several months, and SSC activity was lost by rapid senescence (Schmidt et al 2011). Moreover, the batch of the bovine serum albumin (BSA) greatly influences the success of culture, which limits the potential applications of the cells.…”
Section: Derivation Of Gs Cells In a C57bl/6 (B6) Backgroundmentioning
confidence: 99%
“…Whereas previous studies were based on C57BL/6 (B6) mice, we used DBA/2 mice. GS cells are easily derived from the latter strain and proliferate for at least 2 years without significant changes in SSC activity Kanatsu-Shinohara et al, 2005a), whereas those from B6 mice exhibit an almost 10-fold decrease in SSC activity by 14-18 months and do not proliferate under the current culture conditions (Kanatsu-Shinohara et al, 2003b;Schmidt et al, 2011). Although both GDNF and FGF2 activated the MAP2K1 pathway, augmentation of GDNF signaling by GFRA1 is thought to be necessary to derive SSC cultures from B6 mice (Oatley and Brinster, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although human and mouse SSCs are similar, the fact that human SSCs can not be maintained in the culture systems identical to the mouse system indicates that differences between human and mouse SSCs exist (Schmidt et al 2011). The present study indicated that 20 ng/ml GDNF combined with 1,000 U/ml LIF was the optimal factor combination which could significantly enhance theproliferation of mouse SSCs in vitro.…”
Section: Discussionmentioning
confidence: 99%